2013
DOI: 10.1021/om3011239
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation into the Mechanism of Ethylene Polymerization by a Cationic Dinuclear Aluminum Complex: A Longstanding Unresolved Issue

Abstract: The mechanism for the polymerization of ethylene via a mononuclear aluminum catalyst has been shown previously to lead to inconsistent results. We propose here for the first time a plausible mechanism involving a dinuclear aluminum species which overcomes the problems of the mononuclear catalyst. With the aid of computational quantum chemistry, we have shown that the dinuclear pathway has a much lower activation energy than the mononuclear pathway, a result which can be explained in terms of a greater orbital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Despite a number of cationic aluminum compounds being known, and having noteworthy applications in catalysis, all aluminum-based FLPs have so far been based upon neutral precursors. In the late 1990s, Jordan and co-workers reported a series of highly Lewis acidic, cationic aluminum compounds, with the objective of developing new catalysts for olefin polymerization, the mechanism of which is still a matter of debate. , Of particular interest to us was the complex [DIPP-nacnacAlMe] + [B­(C 6 F 5 ) 4 ] − ( 1 , DIPP-nacnac = [HC­{C­(Me)­N­(2,6- i Pr 2 C 6 H 3 )} 2 ] − ), which was isolated base-free. Although one fluorine atom of the diffuse [B­(C 6 F 5 ) 4 ] − anion coordinates to aluminum in the solid state, in solution compound 1 can be considered to be coordinatively unsaturated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a number of cationic aluminum compounds being known, and having noteworthy applications in catalysis, all aluminum-based FLPs have so far been based upon neutral precursors. In the late 1990s, Jordan and co-workers reported a series of highly Lewis acidic, cationic aluminum compounds, with the objective of developing new catalysts for olefin polymerization, the mechanism of which is still a matter of debate. , Of particular interest to us was the complex [DIPP-nacnacAlMe] + [B­(C 6 F 5 ) 4 ] − ( 1 , DIPP-nacnac = [HC­{C­(Me)­N­(2,6- i Pr 2 C 6 H 3 )} 2 ] − ), which was isolated base-free. Although one fluorine atom of the diffuse [B­(C 6 F 5 ) 4 ] − anion coordinates to aluminum in the solid state, in solution compound 1 can be considered to be coordinatively unsaturated.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions with 4 equiv of AlMe 3 at ambient temperature gave the tetranuclear complexes, in which two additional AlMe 3 molecules are coordinated by either the inner or the outer imine center of the amidinate group. Neutral as well as cationic aluminum amidinate complexes have been investigated in the past as catalyst in different catalytic processes such as olefin polymerization , as well as in the ring-opening polymerization (ROP) of cyclic esters such as lactide and ε-caprolactone …”
Section: Introductionmentioning
confidence: 99%
“…[13] Theoretical investigations have suggested that a cationic dinuclear aluminum species could be a true active species. [14,15] These studies have implied that the direct propagation of ethylene on alkyl aluminum may be realized even under mild conditions if appropriate surroundings is arranged at the aluminum center. Herein, we report experimental and computational study on the polymerization of ethylene catalyzed by the 2 a/Al( i Bu) 3 system and propose hitherto an unknown mechanism, that is different from those of above mentioned CCTP or aufbau type reactions.…”
Section: Introductionmentioning
confidence: 99%
“…reported polymerization of ethylene under milder conditions (60 °C, 0.2 MPa of ethylene) by cationic methyl aluminum complexes with amidinate ligand [13] . Theoretical investigations have suggested that a cationic dinuclear aluminum species could be a true active species [14,15] . These studies have implied that the direct propagation of ethylene on alkyl aluminum may be realized even under mild conditions if appropriate surroundings is arranged at the aluminum center.…”
Section: Introductionmentioning
confidence: 99%